Construção e analise de desempenho de um sistema de aquecimento solar de água utilizando placa de policarbonato como superfície absorvedora - Sodré, Dilton (2010)
It was studied a system for heating water to be used to obtain water for bathing at home, the absorbing surface of the collector is formed by one plate of polycarbonate. The polycarbonate plate has 6 mm thick, 1.050 mm wide and 1.500 mm long with an area equal to 1,575 m². The plate was attached by its edges parallel to PVC tubes of 32 mm. The system worked under the thermo-siphon and was tested for two configurations: plate absorber with and without isolation of EPS of 30 mm thick on the bottom surface in order to minimize heat losses from the bottom. The tank's thermal heating system is alternative and low cost, since it was constructed from a polyethylene reservoir for water storage, with a volume of 200 liters. Will present data on the thermal efficiency, heat loss, water temperature of thermal reservoir at the end of the process simulation and baths. Will be demonstrated the feasibility of thermal, economic and material pickup proposed for the intended purpose.